Effects of happy and sad facial expressions on the perception of time in Parkinson's disease patients with mild cognitive impairment. Issue 2 (7th February 2018) - Mioni, Giovanna; Grondin, Simon; Meligrana, Lucia; Perini, Francesco; Bartolomei, Luigi; Stablum, Franca
ABSTRACT: Introduction: Parkinson's disease (PD) is a movement disorder caused by deterioration of the dopaminergic system. Previous studies have demonstrated temporal as well as emotional facial recognition impairment in PD patients. Moreover, it has been demonstrated that emotional facial expressions alter temporal judgments. In the present study, we investigate the magnitude of temporal distortions caused by the presentation of emotional facial expressions (happiness, sadness, and neutral) in PD patients with mild cognitive impairment (PD-MCI) and controls. Method: Seventeen older adults with PD-MCI and 22 healthy older adults took part in the present study. Participants were tested with a time bisection task with standard intervals lasting 400 ms and 1600 ms. Moreover, a complete neuropsychological evaluation was conducted to characterize the sample. Results: Differences between groups were observed indicating a general underestimation of time in PD-MCI patients. Temporal impairments in PD-MCI patients seem to be caused mainly by a dysfunction at the level of reference memory. The effect of emotional facial expressions on time perception was evident in both PD patients and controls, with an overestimation of perceived duration when happiness was presented and an underestimation when sadness was presented. Conclusion: Overall, our results indicate that reduced cognitive abilities might be responsible for the lower temporal ability observed in PD-MCI patients. Moreover, similar effects of emotional stimuli were observed in both PD-MCI patients and controls.